2020
DOI: 10.1146/annurev-publhealth-040119-094230
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Refugee Children and Youth: Epidemiology, Interventions, and Future Directions

Abstract: The number of refugee youth worldwide receives international attention and is a top priority in both academic and political agendas. This article adopts a critical eye in summarizing current epidemiological knowledge of refugee youth mental health as well as interventions aimed to prevent or reduce mental health problems among children and adolescents in both high- and low-to-middle-income countries. We highlight current challenges and limitations of extant literature and present potential opportunities and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 90 publications
4
73
0
6
Order By: Relevance
“…Additionally, most interventions focus on symptomreduction: much less is known about targeting psychological resilience and affective development -an approach which might be particularly beneficial to refugee children (Panter-Brick et al, 2018;Yaylaci, 2018;Foka et al, 2020). As the number of scalable, cost-effective interventions involving training lay volunteers, schoolteachers, and community workers increase and become more accessible (Fazel, 2018), it is important to develop programs which incorporate varied approaches and which are developed for younger children (Yaylaci, 2018;Frounfelker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most interventions focus on symptomreduction: much less is known about targeting psychological resilience and affective development -an approach which might be particularly beneficial to refugee children (Panter-Brick et al, 2018;Yaylaci, 2018;Foka et al, 2020). As the number of scalable, cost-effective interventions involving training lay volunteers, schoolteachers, and community workers increase and become more accessible (Fazel, 2018), it is important to develop programs which incorporate varied approaches and which are developed for younger children (Yaylaci, 2018;Frounfelker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Others have sounded calls for research in high income countries to focus on several particular issues, including task-shifting approaches that rely upon peer-led interventions, telepsychiatry and e-mental health interventions, and more basic science investigating the neurobiological mechanisms involved in the treatment of PTSD ( 91 ). There is also a need for more work on developing effective interventions for displaced women and children ( 9 , 93 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Refugee women are also at a greater risk for intimate partner violence ( 81 ), which is also associated with risk of mental disorder ( 82 ). Reviews have confirmed the harmful effects that conflicts and forced migration can have on children and adolescents, as well as their caregivers ( 9 , 83 ). In fact, a younger age at time of migration may put refugees at greater risk of mental health difficulties ( 7 ), and there appears to be a dose-response relationship between trauma exposure and severity of PTSD in children ( 84 ).…”
Section: Forced Migration and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Acculturative stress may be exacerbated by the receiving community, through microaggressions or discrimination, and by the heritage community, when some members disapprove of an individual’s process of change [ 9 ]. In the U.S., newcomers from the MENA region, in particular, may encounter identity-based discrimination, such as Islamophobia and anti-Arab sentiment, while also being subject to racialization [ 10 , 11 ]. Additionally, refugees with prior exposure to armed conflict and forced migration may continue to suffer from prior adverse life events, such as witnessing violence, family separation, and protracted displacement [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%